اسلوب الإرشاد الانتقائي في الحد من ظاهرة التنمر الإلكتروني لدى طلبة الثانوية من وجهة نظر المرشدين التربويين في محافظة ميسان - خلف، علي محمود (الجامعة العراقية - مركز البحوث والدراسات الإسلامية, 2023)
The current study aimed to reveal the levels of cyberbullying among high school students from the viewpoint of educational counselors in Maysan Governorate. And also the detection of mean scores for bullying males and average scores for bullying females. Are there statistically significant differences in electronic bullying between members of the experimental group and members of the control group due to the application of the selective counseling program designed by research? The researcher used the descriptive and analytical approach as well as the quasi-experimental method in order to examine the effect of the independent variable. The questionnaire was conducted on (180) students (males and females) who represent the secondary stage in the Education Directorate in the governorate. The study found the weak existence of electronic censorship on what is published on the Internet, as well as the lack of religious preachers among adolescents, which causes them to cause harm to others, as well as the lack of parental and parent control over adolescents, which leads to harm to others. And males are more practicing electronic bullying than females. There are no statistically significant differences at the level of significance (0.05) between the mean scores of the experimental and control group from the research sample on the electronic bullying scale, where the value of the significance level was equal to (0,893), which is a value greater than 0.05, which fulfills the acceptance of the hypothesis.
Keywords: ظاهرة التنمر -- التنمر الإلكتروني -- طلبة المرحلة الثانوية -- المرشد التربوي -- العراق